Igneous petrology - Hughes, Charles J. (Charles James), 1931- (Developments in petrology, 1982)
A balanced text that bridges the gap between introductory petrography-oriented texts and the more advanced texts that have a thermodynamic and/or chemical approach. Well-indexed, well-referenced and written in a particularly readable style, it leads the reader from classical to modern concepts in igneous petrology.